Improving Teachers' Competence in Making Digital Literacy Teaching Modules at School Through Workshops - Ledya Fitriyani; Manap Sumantri; Sumarsih (Universitas Bengkulu, 2024)
The objectives of this study are 1) To describe teachers' competence in making digital literacy teaching modules before the workshop at SMPN 24 Bengkulu Tengah. 2) Developing alternatives for making digital literacy teaching modules to improve teacher competence through workshops at SMPN 24 Bengkulu Tengah. 3) Proving that teachers' digital literacy teaching modules can be improved through workshops at SMPN 24 Central Bengkulu. This research used qualitative research procedures. The test was conducted in at least three cycles, which included planning activities (plan), implementation (act), observation (observe) and reflection (reflect). The subjects in this study were all teachers of SMPN 24 Central Bengkulu. The data analysis technique used qualitatively in this study was carried out by interpreting the data on the results of observations made during the coaching process, as well as the achievement of success indicators from the workshop results of each cycle. the conclusions of this study are as follows: 1) The description of the ability of teachers in making digital literacy teaching modules, the majority of teachers at SMPN 24 Bengkulu Tengah have a less than optimal level of ability. This shows the need for further efforts in training and mentoring teachers in improving their ability to make digital literacy teaching materials. 2) Efforts to improve teacher competence in making digital literacy teaching modules at SMPN 24 Bengkulu Tengah are carried out through workshops. 3) Making digital literacy teaching modules through workshops is successful in improving teacher competence in making teaching modules for teachers at SMPN 24 Bengkulu Tengah. This is indicated by the score of the observation of teachers which continues to increase from cycle 1 to cycle 3. In cycle 1 the score obtained was 178 points or 70.63%, then increased in cycle 2 to 212 points or 84.12%, and the maximum score achievement was 240 points or 95.23% which occurred in cycle 3.